POLICE USE OF INFORMATION TECHNOLOGIES IN CRIMINAL INVESTIGATIONS - Hekim, Hakan; Gul, Serdar K.; Akcam, Bahadır K. (European Scientific Journal, ESJ, 2013)
The purpose of this study is to analyze whether information technologies contribute to the outcome of criminal investigations. The study is a cross-sectional one and its unit of analysis is U.S police departments. Clearance rates of Part I crimes are used as the outcome variable and its independent variable is an index variable constructed by using survey items. After controlling the descriptive analysis results, bivariate and multivariate analyses conducted to examine the relationship between dependent and independent variables. Results showed that the relationship between clearance rates and departmental use of information technologies is not significant. However, this result must be interpreted cautiously because first the independent variable of this study measures whether the responding police departments use or do not use particular kind of information technologies. It does not measure the variability in the quality and intensity of use. Second, the survey data is unbalanced; therefore, it introduces limitations to the multivariate analysis. On the other hand, This study shows that information technologies should be targeted to the policing fields where they would be most effective. In case of criminal investigations, primary investigation phase looks promising. It also argues that process evaluations should be conducted to ensure proper implementation and use of information technologies by police departments.